Respiratory inflammation and infections in high performance athletes - Gleeson, M.; Pyne, D. B. (Immunology & Cell Biology, 2015)
Upper respiratory illness is the most common reason for non-injury related presentation to a sports medicine clinic, accounting for 35-65% of illness presentations. Recurrent or persistent respiratory illness can have a negative impact on health and performance of athletes undertaking high levels of strenuous exercise. The cause of upper respiratory symptoms (URS) in athletes can be uncertain but the majority of cases are related to common respiratory viruses, viral reactivation, allergic responses to aeroallergens, and exercise-related trauma to the integrity of respiratory epithelial membranes. Bacterial respiratory infections are uncommon in athletes. Undiagnosed or inappropriately treated asthma and/or allergy are common findings in clinical assessments of elite athletes experiencing recurrent URS. High performance athletes with recurrent episodes of URS should undergo a thorough clinical assessment to exclude underlying treatable conditions of respiratory inflammation. Identifying athletes at risk of recurrent URS is important in order to prescribe preventative clinical, training and lifestyle strategies. Monitoring secretion rates and falling concentrations of salivary IgA can identify athletes at risk of URS. Therapeutic interventions are limited by the uncertainty of the underlying cause of inflammation. Topical anti-inflammatory sprays can be beneficial for some athletes. Dietary supplementation with bovine colostrum, probiotics and selected antioxidants can reduce the incidence or severity of URS in some athletes. Preliminary studies on athletes prone to URS indicate a genetic predisposition to a pro-inflammatory response and a dysregulated anti-inflammatory cytokine response to intense exercise as a possible mechanism of respiratory inflammation.